2022
DOI: 10.2196/31327
|View full text |Cite
|
Sign up to set email alerts
|

Personalization of Intervention Timing for Physical Activity: Scoping Review

Abstract: Background The use of sensors in smartphones, smartwatches, and wearable devices has facilitated the personalization of interventions to increase users’ physical activity (PA). Recent research has focused on evaluating the effects of personalized interventions in improving PA among users. However, it is critical to deliver the intervention at an appropriate time to each user to increase the likelihood of adoption of the intervention. Earlier review studies have not focused on the personalization of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…It was also found that these three constructs merge into a single construct, rather than acting independently. This finding suggests that knowledge acquisition is one of the contributing factors to evaluating user acceptance (Chaudhari et al. , 2022; Hoehle and Venkatesh, 2015; Lynch et al.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…It was also found that these three constructs merge into a single construct, rather than acting independently. This finding suggests that knowledge acquisition is one of the contributing factors to evaluating user acceptance (Chaudhari et al. , 2022; Hoehle and Venkatesh, 2015; Lynch et al.…”
Section: Discussionmentioning
confidence: 93%
“…It was also found that these three constructs merge into a single construct, rather than acting independently. This finding suggests that knowledge acquisition is one of the contributing factors to evaluating user acceptance (Chaudhari et al, 2022;Hoehle and Venkatesh, 2015;Lynch et al, 2019;Mayer, 2002). When assessing the acceptance of a specific function of WWD, knowledge, usefulness and ease of use are interconnected within a single psychometric property.…”
Section: Health and Fitness Features Of Wrist-worn Wearablesmentioning
confidence: 99%
See 3 more Smart Citations